2018
DOI: 10.3390/s18020414
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Kalman Filter in the Gauss-Helmert Model for Reliability Analysis in Orientation Determination with Smartphone Sensors

Abstract: Abstract:The topic of indoor positioning and indoor navigation by using observations from smartphone sensors is very challenging as the determined trajectories can be subject to significant deviations compared to the route travelled in reality. Especially the calculation of the direction of movement is the critical part of pedestrian positioning approaches such as Pedestrian Dead Reckoning ("PDR"). Due to distinct systematic effects in filtered trajectories, it can be assumed that there are systematic deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Moreover, they integrated a model to limit outliers in the measurement data and to resist negative effects of state model disturbances. Ettlinger et al [ 40 ] observed systematic deviations present in the data obtained from sensors. Their research is focused on an analysis of a measure for the reliability (so-called partial redundancies), i.e., how well systematic deviations can be detected in single observations, and the behavior of partial redundancy by modifying the stochastic and functional model of the Kalman filter.…”
Section: Solution Background and Related Workmentioning
confidence: 99%
“…Moreover, they integrated a model to limit outliers in the measurement data and to resist negative effects of state model disturbances. Ettlinger et al [ 40 ] observed systematic deviations present in the data obtained from sensors. Their research is focused on an analysis of a measure for the reliability (so-called partial redundancies), i.e., how well systematic deviations can be detected in single observations, and the behavior of partial redundancy by modifying the stochastic and functional model of the Kalman filter.…”
Section: Solution Background and Related Workmentioning
confidence: 99%
“…Indirect 4 georeferencing comprises methods where the pose of the MSS is determined by measurements towards known targets. These targets may be flat markers with a specific pattern (Abmayr et al 2008) or simple 3D geometries, such as cylinders or spheres (Elkhrachy and Niemeier 2006). The position of the targets within the superordinate coordinate system is determined using an external sensor, for example, a total station.…”
Section: Georeferencing Of Mss/uasmentioning
confidence: 99%
“…Regarding the steady holding modes, the device attitude heading should be estimated first by fusing the aforementioned sensor data. The fusion is always by means of complementary filters (CFs) [ 10 , 11 , 12 ] and Kalman filters (KFs) [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The system was fixed on waist of pedestrian and the quadrotor unmanned aerial vehicle (UAV) to test the heading estimation accuracy, and the results show that the mean heading estimation errors are less than 10° and 5° respectively. Ettlinger et al [ 17 ] found that the systematic deviations in the observed data caused significant divergence between the estimated and the reference trajectory, and thus proposed a Gauss-Helmert model-based Kalman filter for reliability analysis in orientation determination with smartphone sensors. Deng et al [ 4 ] proposed a quaternion-based EKF for heading estimation using smartphone-embedded sensors.…”
Section: Introductionmentioning
confidence: 99%